Sustainable Development : the Challenge of Transition - Schmandt, Jurgen; Ward, C. H. (Calvin Herbert), 1933-; Hastings, Marilu (Cambridge University Press, 2000)
"Demographers predict that world population will double to around 12 billion people during the first half of the twenty-first century and then begin to level off. Based on this scenario, Sustainable Development: The Challenge of Transition examines what societal changes must occur over the next generation to ensure a successful transition to sustainability. A successful transition must provide for the needs of these people within the constraints of the natural environment. An array of prominent authors presents a broad discussion of the dimensions of sustainable development: not just economic and environmental, but also spiritual and religious, corporate and social, scientific and political. Unlike other books on the subject, this volume provides insightful policy recommendations about how business, government, and individuals must change their current values, priorities, and behavior to meet these challenges. These types of changes ordinarily take many decades to occur, so it is important to begin making them now, before the problems are overwhelming and more costly. This volume will appeal to scholars and decision makers interested in global change, environmental policy, population growth, and sustainable development, and also to corporate environmental managers."--Publisher's description